International and European Security Law - Herbach, Jonathan (Utrecht Journal of International and European Law, 2012)
Security law, or more comprehensively conflict and security law, on the international level represents the intersection of three distinct but interrelated fields: international humanitarian law (the law of armed conflict, jus in bello), the law of collective security (most identified with the United Nations (UN) system, jus ad bellum) and arms control law (including non-proliferation). Security in this sense is multifaceted - interest security, military security and, as is often referred to in the context of the EU, human security. As such, the law covers a wide range of specific topics with respect to conflict, encompassing the use of force, including choice of weapons and fighting techniques, extending to the rules applicable in peacekeeping and peace enforcement, and yet also dictating obligations outside the context of conflict, such as safeguarding and securing dual-use materials (those with both peaceful and military applications) to prevent malicious use.